Perlindungan Hukum Terhadap Anak Korban Perundungan di Lingkungan Sekolah - Hadibah Zachra Wadjo; Denny Latumaerissa; Judy Marria Saimima; Patrick Corputty (AIWADTHU: Jurnal Pengabdian Hukum, 2023)
Introduction: Bullying can happen anytime and anywhere, both in the real world such as at school, at home, in restaurants, or in cyberspace, and can also happen to anyone, including school students.Purposes of Devotion: This service activity aims to find out about bullying, the types and juridical consequences of bullying so as to form understanding and legal awareness for PKM participants. Method of Devotion: Carrying out legal counseling activities in Talaga Hamlet, Piru, West Seram, through panel discussions in which the speaker conveys the material then followed by a question and answer session between the presenter and the participants.Results of the Devotion: Children as the nation's successors must be protected in their growth and development, including from crime or bullying/bullying. Legal protection for children who are victims of the crime of bullying is contained in Article 76C of Law Number 35 of 2014 concerning Child Protection, which substantially accommodates the prohibition against committing violence against children, then legal protection for children who are victims of bullying is not enough only through only repressive efforts, but it is much more effective if there are preventive efforts carried out, one of which is through legal counseling activities that must be carried out on an ongoing basis to foster legal understanding and awareness, as well as the active role of the school, parents and the surrounding community is very important to apply in life.